Success Factors for IoT and Big Data Analytics in Transpiration System: A Systematic Literature Review - Waleed Noori Hussein; Mohammad Rezal Hamzah; L. M. Kamarudin; N. A. Ishak, (Journal of Human Development and Communication (JoHDeC), 2025)
Internet of Things (IoT) envisages overall merging of several “things” while utilizing the internet as the backbone of the communication system to establish a smart interaction between surrounding objects and people. Big data analytics, being the crucial component of IoT, provides valuable platforms through the cloud to manage and analyze data. This paper presents a systematic literature review that is used in identifying the elements of the implementation success factors for the big data analytics and IoT-oriented transportation system. This paper presents the protocol used of the systematic literature review in gathering available and related information for a study being investigated and summarizing empirical evidence for the research.